Differing terminology used to describe antimicrobial resistance can influence comprehension and subsequent behavioural intent - Kate Grailey; Ailidh Finlayson; Bobby Stuijfzand; Clare McCrudden; Adam Jones; Elena Meyer zu Brickwedde; Helen Brown; Sarah Huf; Hannah Behrendt; Ara Darzi (Communications Medicine)
Abstract Background Despite global campaigns, the public’s understanding of antimicrobial resistance (AMR) as a global emergency remains limited. Behaviour change is crucial in preserving antimicrobials but requires improved understanding of AMR at a population level. Methods Members of the public co-designed intervention arms, selecting three alternatives to AMR to be evaluated in a four-armed online randomised behavioural experiment. The primary outcome was attitudes towards AMR. Secondary and exploratory outcomes included comprehension, behavioural intent and recall. Results In April 2024, 4296 participants completed the online survey. Antibiotic Resistance is the most effective terminology for attitudes towards AMR (p < 3.95E-06), comprehension (p = 0.013) and recall (p < 0.0003). Both Antibiotic Resistance and The Antibiotic Crisis reduce behavioural intent to stop a course of antibiotics early. Conclusions Alternative terminology to describe AMR can impact attitudes, comprehension and behavioural intent towards antimicrobial use. Co-designing such terminology with the public can be an effective way utilising meaningful language in public health campaigns.